Preliminary note on the metamorphic conditions around Lutzow-Holm Bay, East Antarctica - Suzuki, Morihisa (1983)
P(論文) The metamorphic conditions in the Lutzow-Holm Bay region during the main phase of the granulite facies metamorphism (perhaps around 1000Ma) are preliminarily estimated by the use of experimentally determined mineral breakdown curves and of some geothermometers and geobarometers. Calculated conditions are in the range of 725±25℃ and 6.3±1.3kb. The values suggest that the region has undergone metamorphic conditions similar to Molodezhnaya Station and Prince Charles Mountains, each of which is considered to belong to the zone affected by the granulite facies metamorphism around 1000Ma. The metamorphic conditions estimated here seem to be compatible also with those in the western part of the Prince Olav Coast. departmental bulletin paper